The Influence of Long Red Blue Led Illumination on the Growth of Pakcoy (Brassica rapa L.) - Samur, Gregorius Adelbertus; Wijaya, I Made Anom Sutrisna; Sulastri, Ni Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Pakcoy (Brassica rapa L.) is an important vegetable in Asia. Red-blue light-emitting diode (LED) illumination can accelerate photosynthesis and influence plant growth. This study aimed to determine the optimal duration of red-blue LED irradiation for pakcoy growth. A completely randomized design (CRD) was used with five irradiation durations: 18, 16, 14, 12, and 10 hours. Observed parameters included plant height, canopy area, number of leaves, chlorophyll content (SPAD value), fresh weight at harvest, biomass, and root length. The results showed that 18 hours of red-blue LED irradiation produced the best growth, with an average plant height of 17.4 cm, 11.5 leaves, chlorophyll content of 43.7 SPAD units, root length of 28 cm, fresh canopy and root weight of 18.25 g and 0.95 g, and trunk and root biomass of 1.21 g and 0.25 g, respectively. In conclusion, prolonged red-blue LED irradiation significantly improves pakcoy growth.